Study of prevalence and clinical spectrum of seizures in children in a teaching hospital in rural Telangana, India - Sastry, C. P. V. Ramana; Reddy, R. Manohar (International Journal of Contemporary Pediatrics, 2018)
Background: To study the prevalence and clinical spectrum of seizures and treatment outcome in children. Methods: A hospital based prospective study was done at Maheshwara Medical College and Hospital, Patancheru, Telangana in the department of Paediatrics over one-year period. A total of 75 cases presenting with seizures were studied for demographics, clinical features, imaging studies where possible and patient response to treatment. Results: T Patient age ranged from one week to 14 years with male to female ratio of 1:4. Majority were in the age group of 1-3 years 25/75 (33.3%). Fever was present on admission in 66.6% of cases in 1 month to 6 years. Unprovoked seizure was common 20/75 (26.6%) in age group 6 to14 years. Neonatal seizures were seen in 6.6% cases. Generalized tonic clonic seizures were common and were seen in 63.3% cases. Only 5 (6.6 %) cases presented with status epilepticus. CT scan was done in 20 cases in unprovoked seizures and showed various etiologies. Conclusions: Seizures in children are a common indication for hospital admission. They can be febrile or unprovoked. CNS infections and space occupying lesions are common causes for paediatric seizures. Early detection of the cause of seizures helps in instituting appropriate treatment. Children with unprovoked seizures should be on regular long term follow up and treatment.